Moral Education Values In Washoya Al Abaa' Lil Abnaa' And Its Relevance To Character Education - Muhlishotin Muhlishotin; Abdul Muhid (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
Abstract: The purpose of this study was to examine the value of moral education in the book Washoya Al Abaa' Lil Abnaa' . The focus of the discussion in this study is how the moral education contained in the book Washoya Al Abaa' Lil Abnaa'. Moral education is the most important thing in education because with morals students will give birth to a religious person, close to God, and so on. This study uses a type of library research by looking at the texts contained in the book Washoya Al Abaa' Lil Abnaa'. The object of this research is explored in the book washoya al abaa' lil abnaa' by using a content analysis approach. The results of this study indicate that the moral education contained in the book Washoya Al Abaa' Lil Abnaa' has several criteria, including 1) Fear of Allah. 2) Rights and Duties towards Allah and His Messenger. 3) Rights and obligations towards both parents. 4) Rights and Obligations towards Friends. 5) Adab in Seeking Knowledge. 6) Learning etiquette, Review and Discussion. 7) The etiquette of eating and drinking. 8) Assembly and Meeting etiquette